ANALISIS FENOMENA DIGITAL FATIGUE PADA SISWA DALAM PEMBELAJARAN BERBASIS TEKNOLOGI: FAKTOR PENYEBAB DAN STRATEGI PENANGANAN - Kaotsar Assofia; Muhammad Zidan Al Faidl; Nur Maulidiyah; Risalatul Muawanah; Ika Mustaufiqoh; Muhammad Rifqi Azizi (STKIP Subang, 2026)
The increasingly widespread use of technology in learning has given rise to the phenomenon of digital fatigue, which affects students’ physical, psychological, and academic well-being. This study aims to analyze research trends, contributing factors, and strategies for addressing digital fatigue among students in the context of technology-based learning. The method used was a Systematic Literature Review (SLR) guided by the PRISMA guidelines, involving a search for articles on Google Scholar indexed in SINTA 1–5 and/or Scopus Q1–Q4, published between 2021 and 2026. Of the 363 articles identified, 7 met the inclusion criteria and were used as the primary sources for analysis. The results of the study indicate that research on digital fatigue continues to evolve, with a shift in focus from exploring its impacts toward identifying causal factors and seeking solutions. Factors contributing to the onset of digital fatigue include excessive screen exposure, high intensity of technology use, cognitive load during online learning, dependence on digital media, and low self-management skills. The identified coping strategies include establishing healthy technology usage habits, practicing digital minimalism, and strengthening support from teachers and schools. This study emphasizes that addressing digital fatigue requires collaboration among students, educators, and schools so that technology can be used optimally without neglecting students’ well-being.